Deletions within a defective suppressor-mutator element in maize affect the frequency and developmental timing of its excision from the bronze locus. - Schiefelbein, J W (1985)
Six independent derivatives of the bz-m13 allele, which contains a 2.2-kilobase-pair defective Suppressor-mutator (dSpm) insertion at the bronze (bz) locus, have been isolated and analyzed. The derivatives were selected for alterations in the frequency and timing of somatic reversion; such derivatives have previously been analyzed genetically and designated "changes in state" by McClintock [McClintock, B. (1955) Carnegie Inst. Washington, Yearb. 54, 245-255]. All of the derivatives analyzed in the present study revert substantially later in development than the original insertion mutation and some show a very low frequency of reversion as well. All of the derivatives contain insertions at the same site as the parent bz-m13 allele. Deletions of 400-1300 base pairs were found in the dSpm elements in four of the six derivatives; the remaining derivatives could not be distinguished structurally from the original mutant allele. The results suggest that changes in the frequency and developmental timing of excision are attributable to alterations in the dSpm element. Furthermore, these data suggest that DNA sequences near the ends of the element are important for responding to the two transacting functions supplied by the transposition-competent Suppressor-mutator (Spm) element.